Was bedeutet Ordnung? Was ordnet Bedeutung? Zu bedeutungskonstituierenden Ordnungsleistungen in Geschriebenem - Noller, Eva Marie (Materiale Textkulturen, 2015)
What does order mean - what orders meaning? These are at once elementary and complex questions for the theoretical and praxeological self-definition of the textual and visual sciences. The collected essays in this volume seek answers from a wide variety of disciplinary and methodological perspectives in relation to both ancient and modern objects. They engage in a dialogue between the notions of "classical" philology and "modern" literary theory.